Mijn leven - Granata, Rocco 1938- (Lannoo, 2013)
Autobiografie van de Italiaanse/Belgische zanger
Met reg
Keywords: Granata, Rocco -- 1938-; Geschichte 1938-; Sänger; Unterhaltungsmusiker; Belgien; Italien; Autobiografie